Evaluation of Students' Creative Thinking Ability in Solving Fraction Problems in Class V of Elementary School - Nurwalidainismawati1, Nurwalidainismawati; Fauzi, Azra (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Students with the ability to think creatively mathematically will receive more attention inside and outside the classroom, but the mathematics learning results obtained by students show unsatisfactory results, especially in solving problems. The objectives of this research are: 1) evaluating students' creative thinking abilities, 2) analyzing factors that inhibit students' creative thinking abilities. This research uses a qualitative type of research using the CIPP approach. The subject of this research was carried out in fifth grade elementary school with sub-subject material regarding fraction calculation operations. Data collection techniques use questionnaires, interviews and test questions. Data validation uses triangulation of sources and methods, with data analysis techniques using 4 research stages from Miles and Hubeman. The results are: 1) evaluation of creative thinking abilities on fluency indicators obtained as a percentage79.04%, flexibility obtained 64.44%, novelty obtained 63.33%, and detail 79.00%, these results show that students are creative in the learning process, not in problem solving activities in questions; 2) the causal factors are low understanding regarding the concept of multiplication calculation operations on fractions with different denominators, highshyness in conveying ideas, lack of practice and involvement in the learning process. In conclusion: the results of the KBK evaluation show that there is a tendency for learning activities to always focus on the teacher, students are more inclined to understand questions based on the example questions that are indicated, the concept of arithmetic operations is not mastered, understanding of the questions is lacking, and they tend to focus on obtaining learning outcomes rather than on the process learning.